2019
DOI: 10.1002/ncp.10427
|View full text |Cite
|
Sign up to set email alerts
|

How Sweet Is This? A Review and Evaluation of Preoperative Carbohydrate Loading in the Enhanced Recovery After Surgery Model

Abstract: Preoperative carbohydrate loading is a contemporary element of the enhanced recovery after surgery (ERAS) paradigm. In addition to intraoperative surgical and anesthetic modifications and postoperative care practices, preoperative optimization is essential to good postsurgical outcomes. What was long held as dogma, a period of prolonged fasting prior to the administration of anesthesia, was later re‐examined and challenged. Along with the proposed physiologic effects of decreasing the surgical stress response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 59 publications
(108 reference statements)
1
32
0
2
Order By: Relevance
“…Nurses and other health care workers should adjust their behavior and encourage patients to eat and drink as long as possible, within the limits of the applicable guidelines. 6 Although evidence shows that preoperative consumption of oral carbohydrate beverages is safe 35 and ERAS protocols include eating recommendations, 44 suggestions for translating this knowledge to daily practice are lacking. 24 Knowledge translation may be difficult in this case because patients are primarily instructed to eat sufficiently within prehabilitation programs.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses and other health care workers should adjust their behavior and encourage patients to eat and drink as long as possible, within the limits of the applicable guidelines. 6 Although evidence shows that preoperative consumption of oral carbohydrate beverages is safe 35 and ERAS protocols include eating recommendations, 44 suggestions for translating this knowledge to daily practice are lacking. 24 Knowledge translation may be difficult in this case because patients are primarily instructed to eat sufficiently within prehabilitation programs.…”
Section: Discussionmentioning
confidence: 99%
“…Contrariwise, the significance of food abstention immediately before surgery is one of the most debated tenets in the field of pre-operative nutritional programs. On the one hand, there appears to be no general association with vomiting or aspiration but, on the other hand, there is a lack of available data on individual surgical procedures [ 28 , 29 ]. Beyond the habit of draw indications from parallel extrapolations, replacing the absolute fasting from midnight with a calorie-loaded supplement up to a few hours before surgery may be a safe element for perioperative care as far as Orthopedics is concerned [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Effects of preoperative carbohydrate loading on the clinical outcomes and prognosis were unidenti ed 31,32 , Smith and the colleagues reviewed all the clinical studies and no positive result was found about the relationship between preoperative carbohydrate and postoperative complication 33 . In addition, the safety of carbohydrate use in patients with diabetes remained uncertain [34][35][36] . Furthermore, our previous study found that the composition proportion of carbohydrate could in uence tumor growth and malignance in mice 37 .…”
Section: Discussionmentioning
confidence: 99%